Prediction Intervals for the Failure Time of Prestressed Concrete Beams - Sebastian Szugat; Jens Heinrich; Reinhard Maurer; Christine H. Müller (Advances in Materials Science and Engineering)
The aim is the prediction of the failure time of prestressed concrete beams under low cyclic load. Since the experiments last long for low load, accelerated failure tests with higher load are conducted. However, the accelerated tests are expensive so that only few tests are available. To obtain a more precise failure time prediction, the additional information of time points of breakage of tension wires is used. These breakage time points are modeled by a nonlinear birth process. This allows not only point prediction of a critical number of broken tension wires but also prediction intervals which express the uncertainty of the prediction.